(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe patient satisfaction with outpatient medical examination and treatment services at the Central Odonto - Stomatology Hospital in Hanoi in 2025 and some related factors. Methods: A descriptive cross-sectional study with analysis. Results: The results showed that the overall satisfaction rate of patients with medical examination and treatment services at the hospital was 93.9%. Among them, the overall satisfaction score regarding the professional aspect of medical staff was the highest, followed by communication attitude, and finally, the facilities and service equipment aspect had the lowest overall satisfaction score. Several factors were identified as being related to overall satisfaction with medical examination and treatment services, including: gender, age, place of residence, marital status, income level, and treatment department, with statistical significance (p < 0.05). Conclusion: The overall satisfaction rate with medical examination and treatment services was 93.9%. Factors related to overall satisfaction with medical examination and treatment services in the study subjects with statistical significance (p < 0.05) included: gender, age, place of residence, marital status, income level, and treatment department.